A sweet and amnesic present: the postcolonial landscape and memory makings in Cape Verde - Sarmento, João (2019)
The construction of memory in landscapes is a complex process which is embedded in webs of political and economic power. Often history is twisted and bended to better serve the current interests of the hegemonic forces at play. In this paper I attempt to explore how memory is at work in three different sites in Santiago Island, Cape Verde: an old fort and a historical town; a concentration camp; and a global resort. The three sites participate in the erasure, maintenance and creation of memory in different ways, forging new forms of collective identity, which are embedded in local as well as global forces and processes. Through an analysis of the changes taking place on these sites, this paper suggests that while the country lives on foreign aid and attempts to embrace neo-liberal practices, it fails not only to provide basic services to the population but to engage critically with its history and geography.